Correlation Between Tax Rates and Tax Revenues in the Ottoman Empire in Respect to Laffer Theorem as Applied to Raki and Wine Figures (1792-1839) - Derviş Koyuncu; A. Mesud Küçükkalay (Belleten)

(untitled)
This study aims to calculate the relationship between tax rates and revenues of wine and raki coming to Istanbul for consumption from different regions of the Ottoman Empire in the period 1792-1839 with the T Test and interpret it according to the Laffer theorem. The main question of the study can be formulated as what kind of change did the increases in the tax rates of wine and raki in 1810, 1822 and 1831 cause in the tax revenue of these goods. This question can also be expressed as whether the Ottoman Empire should or should not increase the tax rates of wine and raki in order to increase tax revenue. In order to achieve this goal and resolve the question, the tax revenues of the period 1792-1839 were obtained from the financial records in various funds of the Presidential Ottoman Archives (BOA) and the changes in these revenues with the change in tax rates were calculated with the T Test. The results of the test will show, according to the Laffer Theorem, whether the Ottoman Empire increased the tax rates of wine and raki, causing an increase or decrease in the tax revenues of these goods, that is, whether the tax rates were above or below the optimum tax rate. The possible result expected to be obtained from this study is that the increase in the tax rates of raki and wine in the Ottoman Empire did not cause an increase in tax revenue, but on the contrary, a decrease. In other words, it can be said that the tax rate increases in these two goods in the Ottoman Empire fell behind the price increases.